Kelimpahan Aedes spp. di kota semarang, purwokerto dan yogyakarta - Nur Endah Wahyuningsih; Edi Dharmana; Endang Kusnawati; Aris Sulistiawan; Edy Purwanto (Jurnal Entomologi Indonesia, 2008)
Abundance of Aedes spp. in Semarang, Purwokerto and Yogyakarta. In Indonesia, Dengue Fever has a high morbidity rate. Incidence Rate (IR) during 39 years (1968-2007) showed a tendency to increase 00-30 per 100,000 populations, but the Case Fatality Rate (CFR) shows a decrease trend from 40% to 1.6%. Method of mosquito control that is mostly done today is chemical control methods. Unfortunately, this method is not always. A survey to find out the composition of the Aedes mosquito species in the field needs to as the first step to improve the method of vector control. This study employed a descriptive survey method, be done, taking eggs and adult mosquitoes from the three cities. From each city. Eggs and adult mosquitoes of Aedes spp from 90 ovitraps and 18 field locations were taken. Eggs obtained from Semarang, Purwokerto and Yogyakarta are 1835, 833, 1345, from 27 (30%), 22 (24,44%) and 25 (27,7%) ovitraps respectively, consisting of species A. aegypti and A. albopictus. A. aegypti and A. albopictus adults obtained in Semarang 17 (5%) and 323 (95%), in Purwokerto 6 (7%) and 81 (93%), while in Yogyakarta, 36 (25%) and 105 (75%) respectively. Research results show that in three cities A albopictus was more abundant than the A. aegypti.